End to end data analytics for product development : a practical guide for fast consumer goods companies, chemical industry and processing tools manufacturers - Salmaso, Luigi; De Dominicis, Mattia; Arboretti, Rosa; Jones, Chris (Christopher Lloyd) (John Wiley & Sons, Inc., 2020)
"Statistical Toolbox for Industrial Applications and Product Development aims to be a reference for practitioners in statistics with an interactive and involving way of exposing contents by making use of both written material and practical examples with specific target on industrial applications. The book will be focussed on Design of Experiments (DoE) targeted for broad industrial applications, but it will cover also basic statistical concepts useful to introduce DoE. It is intended to especially support product innovation and development across fast consumer and pharmaceutical companies in order to improve quality and speed of implementation through data analytics, statistical design and data prediction. The book will promote the use of statistical tools to solve challenges faced during product innovation and feasibility where today is rarely applied. It will also include the following: Innovation feasibility, to formulation and process development; Data correlation between technical lab experiments and consumers feedbacks; Stability studies which are common especially in chemical or pharmaceutical industries ; Regression models. Each chapter will be composed by a first subsection dedicated to the description of an application problem; a second subsection about the description of the statistical solution from the methodological point of view; a third subsection about the use of Minitab for the specific problem under study; a fourth section about other examples and exercises. Each chapter is accompanied by a companion webiste which contains videos summarizing main concepts and application using MINITAB software. In addition, each chapter is accompanied by a link to a quiz session which will guide the reader through a quick revision of his/her understanding of the chapter"--